Konseling Kelompok dengan Metode Mau’idzah Hasanah dalam Mereduksi Kecanduan Game Online (Mobile Legends) - Agung Madya Putra; Kusnadi Kusnadi (Journal of Society Counseling, 2025)
This research discusses "The Role of Group Counseling with the Mau'idzah Hasanah Method in Reducing Online Game Addiction (Mobile Legends) in Kemang Agung Village". Online games offer entertainment and interesting challenges to complete; teenagers are interested in playing without considering the time until they are satisfied. This research aims to reduce online game addiction and determine group counseling using the Mau'idzah Hasanah method to reduce online game addiction. This type of research is field research with a descriptive approach. Data collection tools include interviews, observation, and documentation. Meanwhile, data analysis techniques include data reduction, data presentation, and conclusions or verification. The subjects of this research were 7 teenagers aged 12-21 years. This research method uses the Mau'idzah Hasanah method. Mau'idzah Hasanah is giving advice and giving reminders (warnings) to other people using good language that can convey their hearts, so that the listener is willing to accept the advice. The results of this research show that addiction to online games (mobile legends) can be seen from often speaking rudely to the person you are talking to, lack of sleep, not being able to manage your time, lack of social interaction, often spending money just to top up, and minimal achievement, after carrying out the group counseling process in 4 meetings. The stages of group counseling using the Mau'idzah Hasanah method in reducing addiction to online games (mobile legends) are the initial stage, transition stage, activity stage, and final stage. The success of the mau'idzah hasanah method can also be seen from changes during the group counseling process, including living more productively, being active in community activities and school organizations, being close to the community, being able to understand the character of other people, and listening to what parents say. Sleep more regularly, have a healthier and healthier lifestyle, and don't be negligent in praying.